Point-of-care testing in companion and food animal disease diagnostics - Velayudhan, Binu T.; Naikare, Hemant K. (Frontiers in Veterinary Science, 2022)
Laboratory diagnoses of animal diseases has advanced tremendously in recent decades with the advent of cutting-edge technologies such as real-time polymerase chain reaction , next generation sequencing (NGS), matrix-assisted laser desorption/ionization time - of - flight mass spectrometry (MALDI-TOF MS) and others However, most of these technologies need sophisticated equipment, laboratory space and highly skilled workforce. Therefore, there is an increasing market demand for point-of-care testing (POCT) in animal health and disease diagnostics. A wide variety of assays based on antibodies, antigens, nucleic acid, and nanopore sequencing are currently available. Each one of these tests have their own advantages and disadvantages. However, a number of research and developmental activities are underway in both academia and industry to improve the existing tests and develop newer and better tests in terms of sensitivity, specificity, turnaround time and affordability. In both companion and food animal disease diagnostics, POCT has an increasing role to play, especially in resource-limited settings. It plays a critical role in improving animal health and wellbeing in rural communities in low- and middle-income countries. At the same time, ensuring high standard of quality through proper validation, quality assurance and regulation of these assays are very important for accurate diagnosis, surveillance, control and management of animal diseases. This review addresses the different types of POCTs currently available for companion and food animal disease diagnostics, tests in the pipeline and their advantages and disadvantages.